2020
DOI: 10.3390/s20072158
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Mg Doping Levels on the Sensing Properties of SnO2 Films

Abstract: This work presents the effect of magnesium (Mg) doping on the sensing properties of tin dioxide (SnO2) thin films. Mg-doped SnO2 films were prepared via a spray pyrolysis method using three doping concentrations (0.8 at.%, 1.2 at.%, and 1.6 at.%) and the sensing responses were obtained at a comparatively low operating temperature (160 °C) compared to other gas sensitive materials in the literature. The morphological, structural and chemical composition analysis of the doped films show local lattice disorders a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 50 publications
0
1
0
Order By: Relevance
“…The figure displays lines before the peak separation in red, the overall fitting result in gray, the fitting results for O-Sn 4+ in purple, the fitting results for O-Sn 2+ , the fitting results for V o in purple, and the fitting results for O cem in green. The energy difference between O-Sn 2+ and O-Sn 4+ , O-Sn 2+ and V o , and O-Sn 2+ and O cem were set to 0.7, 1.6, and 2.1 ∼ 2.2 eV, respectively, based on Aragoń et al 54) and Bendahmane et al 55) The O-Sn 2+ peak was observed to be stronger than the O-Sn 4+ peak for the sample with a deposition pressure of 0.3 Pa and f(O 2 ) value of 8%. Moreover, the O-Sn 4+ peak was observed to be stronger than the O-Sn 2+ peak for the sample with a deposition pressure of 0.3 Pa and f(O 2 ) value of 10%.…”
Section: Relationship Between Composition Ratio Control and Sensitivitymentioning
confidence: 99%
“…The figure displays lines before the peak separation in red, the overall fitting result in gray, the fitting results for O-Sn 4+ in purple, the fitting results for O-Sn 2+ , the fitting results for V o in purple, and the fitting results for O cem in green. The energy difference between O-Sn 2+ and O-Sn 4+ , O-Sn 2+ and V o , and O-Sn 2+ and O cem were set to 0.7, 1.6, and 2.1 ∼ 2.2 eV, respectively, based on Aragoń et al 54) and Bendahmane et al 55) The O-Sn 2+ peak was observed to be stronger than the O-Sn 4+ peak for the sample with a deposition pressure of 0.3 Pa and f(O 2 ) value of 8%. Moreover, the O-Sn 4+ peak was observed to be stronger than the O-Sn 2+ peak for the sample with a deposition pressure of 0.3 Pa and f(O 2 ) value of 10%.…”
Section: Relationship Between Composition Ratio Control and Sensitivitymentioning
confidence: 99%
“…The centrifugal force generated by the spinning causes the solution to spread uniformly across the substrate and evaporate, leaving behind a thin film on the surface [17] . MgO:SnO 2 thin films obtained by spin coating have potential applications in various fields, including optoelectronics [18], and gas sensors [19]. The properties of the thin films, such as their thickness, composition, and morphology, can be tuned by adjusting the concentration and ratio of the precursor materials in the solution and the spin-coating parameters, such as spin speed, spin time, and temperature [20].…”
Section: Introductionmentioning
confidence: 99%